Cell contacts are required for induction by cortisol of glutamine synthetase gene transcription in the retina. - Vardimon, L (1988)
In embryonic neural retina the enzyme glutamine synthetase [GS; L-glutamate:ammonia ligase (ADP-forming), EC 6.3.1.2] is a glia-specific differentiation marker inducible with cortisol. We show that cortisol elicits GS mRNA accumulation by stimulating transcription of the GS gene and that this stimulation requires cell contacts: in dissociated and separated retina cells GS gene transcription was not induced; when the separated cells were reassembled into multicellular aggregates, restoring cell contacts, accumulation of GS mRNA was again inducible. In cells dissociated from retina tissue that had been preinduced with cortisol, GS gene transcription rapidly declined, despite continued hormone availability. In the separated cells transcription of the histone H3.3 gene and accumulation of carbonic anhydrase II mRNA were unaffected; therefore, cell separation selectively precluded induction of the GS gene. These findings provide direct evidence for the regulatory role of cell contacts in hormonal control of gene transcription.